The Perception of Senior High School Students in Banyumas District towards Profession and Education of Nursing Bachelor - Handoyo,; Kamaluddin, Ridlwan; Ekowati, Wahyu (Jurnal Keperawatan Soedirman, 2006)
The profession of Nursing has declared it's self as an independent profession in National nursing Workshop in 1983. Nursing profession nowadays is still in the process of professionalism. One effort to support the professionalism of nursing is by carried out a bachelor degree of nursing in universities. The student of senior high school as a row input of bachelor degree of nurse, probably has particular perception about profession and education of nursing bachelor. The Purpose of this research was to find out a description about perception of senior high school students in third grade towards profession and education of nursing bachelor. This research was using a descriptive method. Populations of research were all students of senior high school third grade in banyumas district, annual period of 2005 / 2006. Samples were taken by grade random sampling according groups proportionally. Instrument that used to measure the perception was a stuctured questionnaire with Likert scale. The instrument was tested for itâ€™s reliability and validity. Questionnaire composed with 11 items covering the matter of nursing profession, and 4 items for education of nursing bachelor. The answer of each items furthermore being counted with percentage. Each score was divided with the highest score, then the percentage of each item was consulted with evaluation category by Arikunto (1996). The Result of this research showed that the perception of senior high school students in banyumas district towards profession of nurse, was enough (70,7%). Meanwhile, the perception towards education of nursing bachelor was either enough (71,8%). The conclusion was that the perception of senior high school at third grade in yogyakarta district annual period 2005 / 2006 was good enough.